Determining laser-induced dissociation pathways of multielectron diatomic molecules: Application to the dissociation of O+2 by high-intensity ultrashort pulses - Sayler, A. M.; Wang, P. Q.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2007)
A method for determining the laser-induced dissociation pathways of multielectron diatomic molecules is developed. Despite the abundance of possible dissociation pathways inherent to such molecules, this technique allows one to resolve the dissociation pathways that contribute to the measured intensity-dependent three-dimensional momentum distribution. To illustrate this method, the unique dissociation mechanisms and pathways producing a few predominant features in the laser-induced dissociation momentum distribution of O+2 are determined.